Handbook of Cardiovascular Disease Management in Rheumatoid Arthritis - Semb, Anne Grete (Springer International Publishing : Imprint: Adis, 2017)
This book is a practical and up-to-date review that discusses the impact of traditional cardiovascular risk factors in patients with rheumatoid arthritis, the effect of rheumatoid arthritis disease activity and severity on cardiovascular comorbidity, and the influence of rheumatoid arthritis drug therapy on cardiovascular risk. This title also explores cardiovascular disease as a manifestation of rheumatoid arthritis and highlights the available methods for screening and diagnosing these conditions. Current and emerging therapies to aid clinicians in the daily management of their patients are also featured in this title. Busy healthcare professionals who are looking for a collaborative approach to these conditions will benefit from this comprehensive overview.